2021
DOI: 10.21931/rb/2021.06.01.30
|View full text |Cite
|
Sign up to set email alerts
|

Potential bioactive compounds of medicinal plants against new Coronavirus (SARS-CoV-2): A review

Abstract: Nowadays, COVID-19 cases are growing worldwide, and there is no evidence of an effective drug to combat the new SARS-CoV-2 virus. In this sense, medicinal plants as an alternative treatment are being used without control to handle the pandemic situation. Therefore, bioactive compounds against Coronavirus of medicinal plant species that grow in Ecuador are discussed. The plant species described in this review are Azadirachta indica, Cinchona pubescens, Coriandrum sativum, Cúrcuma longa, Eucalyptus spp, Morus al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…Due to the remoteness, poverty, and lack of modern healthcare facilities, the people of this region strongly believe in this age-old traditional cure system 3 , 39 . In the context of the pandemic Coronavirus disease (COVID-19), medicinal plants are found to be very effective 47 – 49 . Many people affected by the COVID-19 have recovered without hospitalization as they use medicinal plants of their region.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the remoteness, poverty, and lack of modern healthcare facilities, the people of this region strongly believe in this age-old traditional cure system 3 , 39 . In the context of the pandemic Coronavirus disease (COVID-19), medicinal plants are found to be very effective 47 – 49 . Many people affected by the COVID-19 have recovered without hospitalization as they use medicinal plants of their region.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Lau K.-M et al (2018) [6], an oral dose of 250 mg/kg/day of Houttuynia cordata leaf extract could be considered an unobserved side effect level in rats for 28 days. According to Vietnamese Pharmacopeia V [10], Morus alba leaf doses range from 5 g to 12 g in the decoction dosage form.…”
Section: Methods 221 Research On the Formulation Of Hard Capsules Con...mentioning
confidence: 99%
“…In the anti-viral aspect, Houttuynia cordata exhibited significant inhibitory effects on SARS-CoV 3C-like protease and RNA-dependent RNA polymerase [3], [5]. Santana et al (2021) presented a list of different bioactive compounds against SARS-CoV-2 for many medicinal plant species, of which the active ingredient in Morus alba was considered to have great potential [6]. A study by Arm Adel et al (2022) showed that papaya extract had significant effects in the treatment of dengue virus with antiviral, immunomodulatory, and cytokine storm-reducing properties, so it would reduce inflammatory conditions caused by COVID-19 [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of co-adjuvants, such as high doses of vitamin D [ 41 ], intravenous vitamin C [ 42 ], zinc supplements [ 43 ], or medicinal plants and their active components, has been proposed as a supplementary treatment [ 44 ]. They are under investigation, but none have been accepted as being a definitive treatment.…”
Section: Introductionmentioning
confidence: 99%